Survey and Evaluation of Natural Colour Yielding Potential of Himalayan Plant Species - Sharma, R.S.; Mishra, Vandana; Singh, Ram; Seth, Nidhi; Babu, C.R. (Asian Journal of Chemistry, 2016)
The ecological and health hazards associated with the chemical dyes have become a great environmental concern especially for food, cosmetic and pharmaceutical industries. Therefore, the demand and search for new and novel sources of natural colour is increasing. The rich biodiversity of Himalayan ecosystem has not been assessed for their natural colour yielding potential. Hence, to identify the newer sources of colouring matters, surveys of NW Himalaya were carried out and 24 plant species belonging to 19 families were screened for the presence of colouring matter. Different shades of yellow and orange are found to be the most predominant natural colours (66.6%) followed by shades of green (26.6%) and red (6.6%). The UV-Vis spectral characteristics suggested that most of the colouring extracts contain flavonoids, anthraquinone, chlorophyll and carotenoids; however, tannin was also dominating in certain species. Therefore, we suggest that the Himalayan species are a rich source of natural colours and analyses based on extraction of colouring matter in ethanol coupled with UV-Vis spectra can be of immense value in screening the plant species for identification of new and novel sources of natural colours.